Perbedaan Pengaruh Usia terhadap Kemampuan Digital Literacy pada Guru - Wulan Prandari Capri (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the differences in digital literacy skills of teachers based on age. The population in this study are teachers who work in the JABODETABEK area. The sampling technique used purposive sampling in which the sample was taken with certain criteria, while the sample of this study amounted to 162 teachers who served in the JABODETABEK area and were divided into two adult age groups, namely early adulthood and late adulthood. This study uses three indicators from the NG measuring instrument (212), namely can we teach digital native. Data analysis method used in this research is quantitative analysis. The data used are primary data and time series. The results showed that there was no difference in digital literacy skills for early-adult teachers and middle-adult teachers with a significance value of 0.198, while for the average digital literacy ability, early-adult teachers were 67.99 and middle-aged teachers were 65.75. Keywords: Digital Literacy, Teacher, Age